Metabolomic Profile and Antioxidant/Anti-Inflammatory Effects of Industrial Hemp Water Extract in Fibroblasts, Keratinocytes and Isolated Mouse Skin Specimens - Viviana di Giacomo; Lucia Recinella; Annalisa Chiavaroli; Giustino Orlando; Amelia Cataldi; Monica Rapino; Valentina Di Valerio; Matteo Politi; Marco Daniel Antolini; Alessandra Acquaviva; Francesco Bacchin; Massimo Di Mascio; et al. (MDPI AG, 2021)
Industrial hemp is a multiuse crop whose phytocomplex includes terpenophenolics and flavonoids. In the present study, the phenolic and terpenophenolic compounds were assayed in the water extract of the hemp variety Futura 75. Protective effects were also investigated in human fibroblast and keratinocytes and isolate mouse skin specimens, which were exposed to hydrogen peroxide and/or to the extract (1-500 µg/mL). The results of phytochemical analysis suggested the cannabidiol, cannabidiolic acid and rutin as the prominent phytocompounds. In the in vitro system represented by human keratinocytes and fibroblasts, the hemp extract was found to be able to protect cells from cytotoxicity and apoptosis induced by oxidative stress. Moreover, modulatory effects on IL-6, a key mediator in skin proliferation, were found. In isolated rat skin, the extract reduced hydrogen peroxide-induced l-dopa turnover, prostaglandin-E2 production and the ratio kynurenine/tryptpophan, thus corroborating anti-inflammatory/antioxidant effects. The in silico docking studies also highlighted the putative interactions between cannabidiol, cannabidiolic acid and rutin with tyrosinase and indoleamine-2,3-dioxygenase, involved in l-dopa turnover and tryptophan conversion in kynurenine, respectively. In conclusion, the present findings showed the efficacy of hemp water extract as a skin protective agent. This could be partly related to the extract content in cannabidiol, cannabidiolic acid and rutin.